From Economic Crisis to a Crisis of Representation? The Relationship Among Economic Conditions, Ideological Congruence, and Electoral Participation - Navarrete, Rosa M. (Frontiers in Political Science, 2021)
Research indicates that ideological congruence between citizens and political parties increases the likelihood of turning out to vote. But does this relationship also hold in times of economic crisis? In this study, I investigate whether economic conditions moderate the effect of voter–party representation on turnout. I argue that ideological congruence has significant effects on electoral participation during “normal” times, but these are even more relevant when citizens face economic hardship. Thus, in times of crisis, citizens are more likely to vote if they have a party that represents their position. I empirically test this argument by analyzing large-scale cross-national survey data from the Comparative Study of Electoral Systems (CSES). Findings bear important implications for the relationship between economic conditions and the functioning of modern democracies.